STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PRESTASI OLIMPIADE AKADEMIK SISWA DI SMAN 5 MATARAM TAHUN PELAJARAN 2024/2025 - Herlina, Nesti Nadia; Suhardi, Muhamad; Najwa, Lu’luin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Students’ achievement in academic olympiads reflects not only individual competence but also the effectiveness of school-based coaching strategies and leadership. The success of SMAN 5 Mataram in national competitions such as the National Science Olympiad (OSN), Islamic Education Olympiad (PAI), and National Student Sports Olympiad (O2SN) highlights the importance of systematic and sustainable coaching programs. This study aims to analyze the planning, implementation, as well as the supporting and inhibiting factors of the principal’s strategies in improving students’ olympiad achievements at SMAN 5 Mataram in the 2024/2025 academic year. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation. The research participants consisted of the principal, olympiad coaches, and students involved in the coaching program. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the principal’s strategies are systematically planned from the student admission process through interest and talent mapping, implemented through structured coaching outside regular class hours, involving subject teachers and alumni, and supported by adequate school facilities. Supporting factors include the principal’s strong commitment, collaboration among coaches, and students’ motivation, while inhibiting factors involve time constraints, scheduling conflicts, and the high level of difficulty of olympiad materials. The study concludes that directed, collaborative, and adaptive school leadership plays a crucial role in sustainably enhancing students’ olympiad achievements. ABSTRAK Prestasi olimpiade siswa mencerminkan keberhasilan strategi pembinaan yang diterapkan oleh sekolah serta efektivitas kepemimpinan kepala sekolah dalam mengelola program akademik unggulan. Keberhasilan SMAN 5 Mataram dalam meraih prestasi pada ajang Olimpiade Sains Nasional (OSN), Olimpiade Pendidikan Agama Islam (PAI), dan Olimpiade Olahraga Siswa Nasional (O2SN) menunjukkan pentingnya strategi pembinaan yang terencana dan berkelanjutan. Penelitian ini bertujuan untuk menganalisis perencanaan, pelaksanaan, serta faktor pendukung dan penghambat strategi kepala sekolah dalam meningkatkan prestasi olimpiade siswa di SMAN 5 Mataram Tahun Pelajaran 2024/2025. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Informan penelitian meliputi kepala sekolah, guru pembina, dan siswa peserta olimpiade. Data dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi kepala sekolah direncanakan secara sistematis sejak penerimaan peserta didik baru melalui pemetaan minat dan bakat siswa, dilaksanakan melalui pembinaan terstruktur di luar jam pelajaran dengan melibatkan guru pembina dan alumni, serta didukung oleh fasilitas sekolah yang memadai. Faktor pendukung utama meliputi komitmen kepala sekolah, kerja sama guru pembina, dan motivasi siswa, sedangkan faktor penghambat meliputi keterbatasan waktu, benturan jadwal, dan tingkat kesulitan materi olimpiade. Penelitian ini menyimpulkan bahwa kepemimpinan kepala sekolah yang terarah, kolaboratif, dan adaptif berperan penting dalam meningkatkan prestasi olimpiade siswa secara berkelanjutan.